2018
DOI: 10.3389/fimmu.2018.02370
|View full text |Cite|
|
Sign up to set email alerts
|

Co-stimulation With TLR7 Agonist Imiquimod and Inactivated Influenza Virus Particles Promotes Mouse B Cell Activation, Differentiation, and Accelerated Antigen Specific Antibody Production

Abstract: Current influenza vaccines have relatively low effectiveness, especially against antigenically drifted strains, the effectiveness is even lower in the elderly and immunosuppressed individuals. We have previously shown in a randomized clinical trial that the topical application of a toll-like receptor 7 agonist, imiquimod, just before intradermal influenza vaccine could expedite and augment antibody response, including to antigenically-drifted strains. However, the mechanism of this vaccine and imiquimod combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 56 publications
0
17
1
Order By: Relevance
“…The improved antibody response in the MTF-VAC group was associated with a more robust T FH response and a more potent germinal center reaction. This is in contrast with our previous study on the TLR7 agonist, imiquimod, in which there was no difference in the GC reaction between the imiquimod-adjuvanted group and non-adjuvanted group [ 27 ]. T FH cell is the key T cell subtype that interacts with B cells in lymphoid follicles [ 39 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The improved antibody response in the MTF-VAC group was associated with a more robust T FH response and a more potent germinal center reaction. This is in contrast with our previous study on the TLR7 agonist, imiquimod, in which there was no difference in the GC reaction between the imiquimod-adjuvanted group and non-adjuvanted group [ 27 ]. T FH cell is the key T cell subtype that interacts with B cells in lymphoid follicles [ 39 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The hemagglutination inhibition assay (HAI), micro-neutralization assay (MN), and enzyme-linked immunosorbent assay (ELISA) assays were performed as previously described [ 13 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Kwissa et al 21 found that CD14 + CD16 + monocytes, which are induced by dengue virus infection, and by R848 but not CpG, enhance B-cell differentiation, providing another possible explanation for the differential role of monocytes in R848-versus CpG-stimulated B-cell differentiation. The capacity of TLR7/8 agonists to induce B-cell differentiation is also apparent in vivo whereby adjuvanting inactivated influenza vaccine with a TLR7 agonist accelerates B-cell differentiation and antibody secretion in mice 39 and non-human primate neonates. 40 Analogously, inactivated wholevirion influenza vaccine, as opposed to subunit or split virion vaccines, induces TLR7-mediated B-cell activation and increased antibody production in mice.…”
Section: Monocytesmentioning
confidence: 99%
“…The exact mechanism has not been fully understood, but some authors hypothesized a role of the co-stimulation of CD40 ligand-like action expressed by imiquimod cytokines, of the Blimp-1 gene transcription with a strong induction of IgM secretion and of the high capacity of TRL7 to induce naïve B cells into antigen-specific antibody producing cells. 28,29 Adenosine receptor, especially A2A receptor, represents another molecular target of imiquimod. By this, imiquimod inhibits a negative feedback mechanism that normally limits the pro-inflammatory reactions resulting in a synergic effect of TRLs' signal through a maintained production of inflammatory cytokines (Figure 1).…”
Section: Imiquimod Antitumoral Mechanism Of Actionmentioning
confidence: 99%
“…The result is a strong B cells proliferation, activation and production of antigen specific IgM and IgG. The exact mechanism has not been fully understood, but some authors hypothesized a role of the co‐stimulation of CD40 ligand‐like action expressed by imiquimod cytokines, of the Blimp‐1 gene transcription with a strong induction of IgM secretion and of the high capacity of TRL7 to induce naïve B cells into antigen‐specific antibody producing cells 28,29 …”
Section: Imiquimod Antitumoral Mechanism Of Actionmentioning
confidence: 99%